The urgency of developing and validation of sustainability competence instruments for prospective teachers in Indonesia - Abdulkadir Rahardjanto; H. Husamah; Tutut Indria Permana; Nurdiyah Lestari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The urgency of developing and validating sustainability competence instruments for prospective teachers in Indonesia stems from the pivotal role teachers play in embedding sustainable development principles into education. This study aims to analyze this urgency, synthesize key themes, and visualize conceptual relationships using data collected via Scopus AI. Employing a systematic review methodology with advanced keyword searches and thematic qualitative analysis, the study identifies major themes such as assessment tools, teacher education, and education for sustainable development. Findings reveal significant gaps in culturally relevant, validated instruments tailored for Indonesian prospective teachers, alongside challenges including limited technological infrastructure and the need for ongoing professional development. The study concludes that developing robust competence instruments is vital to strengthen teacher training programs in alignment with Sustainable Development Goals (SDGs). The implications highlight the necessity of integrating digital skills, experiential learning, and community engagement to better prepare future educators for sustainability education. This review lays a foundation for future empirical research and policy initiatives aimed at enhancing sustainability competence assessment within Indonesia’s teacher education system.